Carbon footprint and economic performance of dairy farms: The case of protected designation of origin farms in France. (January 2021) - Lambotte, Mathieu; De Cara, Stéphane; Brocas, Catherine; Bellassen, Valentin
Abstract: This paper assesses the drivers of greenhouse gas emissions and economic performances for a sample of dairy farms Protected Designation of Origin dairy farms in France. Investigating caeteris paribus drivers of performance, we conclude that synergies are rare. Investing in farming equipment, optimizing fuel use or suppressing manure composting can however improve environmental performance by 5 to 13% without impairing profits. In parallel, increasing labor productivity and reducing the share of protein in the diet enhances the economic performance by 7 to 21% without increasing GHG emissions. On the debated merit of intensiveness, our analysis leans towards a negative influence of concentrates, especially protein-rich ones such as soybean cakes, both on economic and environmental performances. This result, consistent with previous studies on extensive systems, could be conditioned by a good know-how and management of grass. Highlights: Direct and indirect land use changes modify the carbon footprint of dairy farms. The economic and environmental performances of PDO farms are mostly antagonist. Farming equipment, fuel and manure are related to environmental performance. Labor productivity and the protein rich diet are related to economic performance. No practice creates a synergy between environmental and economic performances.